2014
DOI: 10.1590/s0100-736x2014000700014
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da redução ou substituição do soro fetal bovino por outros compostos na maturação in vitro de oócitos bovinos

Abstract: A utilização do soro fetal bovino (SFB), embora bastante disseminada na produção in vitro (PIV) de embriões bovinos, apresenta limitações por ser um meio indefinido e por causar efeitos que prejudicam a qualidade desses embriões. Por esse motivo, nos últimos anos, grande parte das pesquisas relacionadas à PIV está voltada para a substituição do SFB por outros compostos nos meios de cultura. No presente estudo, foram utilizados como compostos protéicos a albumina sérica bovina livre de ácidos graxos (BSA-FAF) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the M3 experiment, concentrations of 5 and 10% FBS, 0.8% BSA, and the FBS+BSA (5+0.8%) combination were compared. According to Del Collado et al (2014), low FBS concentrations in IVM can generate results similar to those obtained under high FBS concentrations. Thus, the lowest FBS concentration (5%) was used in the medium containing the conjugation of the protein sources.…”
Section: Discussionmentioning
confidence: 81%
“…In the M3 experiment, concentrations of 5 and 10% FBS, 0.8% BSA, and the FBS+BSA (5+0.8%) combination were compared. According to Del Collado et al (2014), low FBS concentrations in IVM can generate results similar to those obtained under high FBS concentrations. Thus, the lowest FBS concentration (5%) was used in the medium containing the conjugation of the protein sources.…”
Section: Discussionmentioning
confidence: 81%
“…The harmful action of high FBS concentrations observed in some studies might be because serum is a compound rich in fatty acids that are easily transported to the oocyte cytoplasm, resulting in an increase in lipids in the oocytes (Del Collado et al, 2014). That situation can be harmful to bubaline embryos, as the presence of abundant cytoplasmic granules, characterized as having a high lipid content, in oocytes of this species has been demonstrated in ultrastructural studies (Boni et al, 1992;Gasparrini, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…Various studies have been performed to investigate the effects of removing FBS in culture systems by replacing it, or lowering its concentration (Feugang et al, 2009), with the use of various supplements (Lim et al, 2007;Mingoti et al, 2011). Del Collado et al (2014) used bovine serum albumin free of fatty acids (BSA-FAF), and a commercial product called embryonic fluid, alone or in different combinations and concentrations, and concluded that it is possible to diminish the concentration of FBS in the IVM medium for cattle to 3.5% without significantly impairing the nuclear and cytoplasmic maturation rates.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the three lipid staining techniques most commonly used were compared in denuded oocytes after the in vitro maturation. Lipid detection by Nile Red appeared to be more efficient because it captured the increase in lipid content that occurs when COCs are matured in culture medium enriched with FCS ( Del Collado et al, 2014 ) in relation to the control constituted by PVA, which is an alcohol that only increases the surface tension without exerting any function on lipolytic activities ( Asada et al, 2002 ). This technique was previously validated in bovine oocytes as being efficient for detection of variations of lipid content in different culture conditions ( Genicot et al, 2005 ; Barceló-Fimbres and Seidel, 2011 ).…”
Section: Discussionmentioning
confidence: 99%